Disseminated Tuberculosis Causing Addisons Disease in an Adult Diabetic Patient - Qureshi, Nazmul Kabir; Latif, Zafar Ahmed (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Tuberculosis may affect many of the endocrine glands including the hypothalamus, pituitary, thyroid with adrenal gland being the commonest. We describe a patient presented with recurrent spontaneous hypoglycemia, hypotension, fever, weight loss and cough. Along with this clinical picture, high ACTH in the face of low cortisol was compatible with diagnosis of Addisons disease. Rapid ACTH stimulation test affirmed the diagnosis. Disseminated TB affecting adrenal glands was supported by CXR, USG, CT Abdomen and FNAC. Adrenal Crisis was led by add-on bacterial pneumonia. Patient made good recovery with treatment for adrenal crisis and subsequently with standard antitubercular regimen and steroid replacement therapy. Tuberculosis, although uncommon but potentially devastating cause of adrenal failure, merits consideration when fever, weight loss, gastrointestinal symptoms, hyponatremia, hyperkalemia are observed in patients with features of active tuberculosis or past history of tuberculosis J Bangladesh Coll Phys Surg 2015; 33(1): 44-47